Efficacy and Safety of SGLT2 Inhibitors as Adjunctive Treatment in Type 1 Diabetes in a Tertiary Care Center in Saudi Arabia - Fallatah, Walla; Brema, Imad; Alobedallah, Ahmed; Alkhathami, Reem; Zaheer, Shawana; AlMalki, Eyad; Almehthel, Mohammed; Alzahrani, Saad; AlMalki, Mussa H. (Avicenna Journal of Medicine, 2022)
Background Adjunctive treatment with sodium-glucose co-transporters 2 inhibitors (SGLT2- I) has been successfully used in patients with type 1 diabetes mellitus (T1DM) in recent years to improve glycemic control and reduce body weight without increasing the risk of hypoglycemia; however, there is a scarcity of evidence for real-world experience in their use in T1DM Saudi patients. The purpose of this study was to evaluate the efficacy and safety of empagliflozin as off-label adjunctive therapy in Saudi patients with T1DM.Methods This study was a retrospective study for T1DM patients, who were prescribed empagliflozin as an adjunctive therapy. Baseline characteristics including age, changes in HbA1c, body weight, total daily insulin dose, lipid profile, and well as side effects such as urinary tract infections (UTIs) and diabetes ketoacidosis (DKA) were evaluated before and after initiation empagliflozin in 37 T1DM patients.Results The mean age was 25.8 ± 8.0 years, mean weight was 75.3 ± 14.8 kg, mean body mass index (BMI) was 28.1 ± 6.7 kg/m2, mean duration of diabetes was 10.1 ± 6.5 years, and mean HbA1c was 9.4 ± 1.4%. After a mean follow-up duration of 15.8 ± 6.0 months, the mean reduction in the HbA1c% from baseline was 0.82% (p = 0.001) and mean weight reduction from baseline was 1.7 kg (p = 0.097). The total daily insulin dose was decreased by 2.9 units. UTIs and DKA episodes were reported among 2.7% and 10.8% of the participants, respectively.Conclusion Empagliflozin in combination with insulin in overweight Saudi T1DM subjects resulted in a significant improvement in glycemic control, mild non-significant reduction in body weight, and a small but statistically significant reduction in the total daily insulin dose with a slight increase in the risk of DKA and UTIs. Further larger prospective studies are needed for better evaluation of the efficacy and safety of these agents in Saudi T1DM patients.
Keywords: type 1 diabetes mellitus; sodium-glucose co-transporter 2 inhibitors; glycemic control; weight gain; diabetic ketoacidosis